Modern Organizational and Economic Aspects and Staffing Issues in Breeding and Seed Production - GULYAEVA, Tatyana I.; SAVKIN, Vladimir I.; KALINICHEVA, Elena Y.; SIDORENKO, Olga V.; BURAEVA, Elena V. (Journal of Environmental Management and Tourism, 2019)
The immediacy of the studied problem is in the actual status of domestic and foreign breeding and seed production. The purpose of the article is to form a modern economic system and to develop new ways of scientifically based process in the organization breeding and seed production. The research methodology was based on the systematization and comparative analysis of problems of high dependence of the Russian agricultural sector on import seeds. The leading approach in the research methodology of this problem is a system analysis based on consideration of the economy of breeding and seed production as an integral complex of interrelated elements. A mechanism for the formation of a modern economic system of breeding and seed production taking into account the directions for the development of domestic breeding and seed production, providing state support for competition, upgrading seed breeding centers, the formation of personnel potential and educational and scientific production complexes for the development of the intellectual potential of Russian breeding and seed production has been proposed. The materials of the article are of practical value for the formation of suitable state policy and ensuring the competitiveness of the scientific potential in breeding and seed production.